Konsep Akulturasi Fikih dan Maslahat Umum dalam Legislasi KHI - Fanani, Zainal (ASASI: Journal of Islamic Family Law, 2022)
The legislation of Islamic jurisprudence into law in Indonesia has attracted a lot of attention, because of the complexity of Islamic jurisprudence law which is founded on several schools of thought as well as considerations of public benefit. Public maslahah are intended to maintain order in community life in order to realize a sense of security, orderliness and justice, especially in relation to religious diversity. Pluralism, which is the motor of religious diversity, sometimes becomes a problem in itself in religion. Gender equality, which is often identified as bad for Islamic law, adds to the legislative complexity of Islamic law in Indonesia. Fiqh legislation in the form of a compilation of Islamic law (KHI) has certainly gone through a long debate in addressing fiqh as the raw material for Islamic law and the general interests of society. So research is needed to look for the concept of acculturation in the KHI in legislation and jurisprudence in the law. This research is library research which uses descriptive qualitative methods with a positive legal and Islamic law approach. With maslahah analysis theory, to find a common ground between jurisprudence and the interests of society (public maslahah). This research focuses on book I in KHI, which discusses marriage. In this research, it was found that the fiqh acculturation system and state interests in KHI were divided into three; 1. Holding a case that does not exist in Fiqh based on maslahah, 2. Rejecting a case that is contrary to the proposition based on the qath'i dilalah. 3. Elaborate on matters whose maslahah are certainly real , even though they conflict with the general opinion of the Ulama'.